EDUCATION QUALITY ASSURANCE AND STANDARDS IN KENYA: OVERSEEING CURRICULUM IMPLEMENTATION AND DELIVERY IN SECONDARY SCHOOLS - A CASE OF TAITA TAVETA - Okoth, John Odhiambo; Maneno, Dr. Robert; Amuka, Dr. Lorna A. (African Journal of Education and Practice, 2018)
Purpose: The study is an Action Research that critically analysed the function of Education Standards and Quality Assurance Council (ESQAC) in Kenya with respect to; overseeing curriculum implementation and delivery in Secondary Schools; particularly in the wake of dismal performance in National Examination by the students in secondary schools. Methods: The location of the study was in Taita Taveta County in Kenya. Purposive sampling was used to select the three ESQAC Officers, while, stratified sampling was used to select 40 secondary schools in Taita Taveta County. Data was collected using Focus Group Discussion Schedules for ESQAC Officers and Questionnaires for Principals of Secondary Schools. Data was analysed using both qualitative and quantitative techniques. Results: The study found that ESQAC officers carried assessment in fewer schools than was expected. That the number of teachers supported by the officers was low and few school follow-up cases by the said officers were reported. These shortcomings were found to be as a result of shortage of officers, limited financial resources and means of communication. Ministry of Education should operationalize ESQAC as Established in article 64 of the Basic Education Act 2013 and given mandate by Legal Notice No. 11, 2014. Unique contribution to theory, practice and policy: The Cabinet Secretary and the Principal Secretary (State Department of Early Childhood and Basic Education) in the Ministry of Education should operationalize ESQAC in article 64 of the Basic Education Act 2013 and given mandate by Legal Notice No. 11, 2014. This would enable parliament and other financing agencies to provide funds that would support ESQAC programs from National level to Taita Taveta County level. The Ministry of Education should through its training agencies introduce training package for those joining ESQAC as Officers and also to provide in-service training for existing Officers.